2018
DOI: 10.1002/ijc.31556
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic activity of the rhabdovirus VSV‐GP against prostate cancer

Abstract: Oncolytic viruses, including the oncolytic rhabdovirus VSV-GP tested here, selectively infect and kill cancer cells and are a promising new therapeutic modality. Our aim was to study the efficacy of VSV-GP, a vesicular stomatitis virus carrying the glycoprotein of lymphocytic choriomeningitis virus, against prostate cancer, for which current treatment options still fail to cure metastatic disease. VSV-GP was found to infect 6 of 7 prostate cancer cell lines with great efficacy. However, susceptibility was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…The combined DNA vaccine provided therapeutic activity by superior inhibition of tumor growth and prolonged survival in a B16 melanoma mouse model compared to immunization with individual SFV DNA vectors. Moreover, therapeutic efficacy was observed after intratumoral administration of an oncolytic pseudotyped vesicular stomatitis virus (VSV-GP), which generated long-term remission in murine prostate cancer models, also in subcutaneous tumors and bone metastases after intravenous administration [11]. Additional studies have confirmed therapeutic tumor regression in lung (MV particles and SFV VLPs), ovarian (oncolytic VSV particles and Sindbis virus VLPs), and pancreatic cancers [1].…”
Section: Preclinical Applications For Cancer Therapymentioning
confidence: 95%
“…The combined DNA vaccine provided therapeutic activity by superior inhibition of tumor growth and prolonged survival in a B16 melanoma mouse model compared to immunization with individual SFV DNA vectors. Moreover, therapeutic efficacy was observed after intratumoral administration of an oncolytic pseudotyped vesicular stomatitis virus (VSV-GP), which generated long-term remission in murine prostate cancer models, also in subcutaneous tumors and bone metastases after intravenous administration [11]. Additional studies have confirmed therapeutic tumor regression in lung (MV particles and SFV VLPs), ovarian (oncolytic VSV particles and Sindbis virus VLPs), and pancreatic cancers [1].…”
Section: Preclinical Applications For Cancer Therapymentioning
confidence: 95%
“…The survival rate was 90% at 12 months in immunized mice compared to control mice, who had either succumbed to prostate cancer or presented a heavy tumor load. In another study, the prostate-specific antigen (PSA) was expressed from a VEE vector showing efficient infection of mouse DCs in vitro and eliciting a robust PSA-specific response in vivo [ 127 ]. Furthermore, immunization with VEE-PSA strongly stimulated production of IgG2a/b anti-PSA antibodies and tumor growth was significantly delayed.…”
Section: Vaccines Against Cancermentioning
confidence: 99%
“…The study showed that immunization can overcome immune tolerance to PSA and can mediate rapid clearance of PSA-expressing tumor cells. Related to VSV vectors, the VSV-GP-LCMV expressing luciferase showed great efficacy of infection of prostate cancer cell lines and long-term remission in Du145 and 22Rv1 prostate cancer models after intratumoral injections [ 127 ]. Moreover, remission was also observed in syngeneic TRAMP-C subcutaneous tumors and after intravenous vector administration in PC-3M-Luc bone metastases.…”
Section: Vaccines Against Cancermentioning
confidence: 99%
“…The response in both subcutaneous and orthotopic xenograft models could be enhanced by combination therapy with ruxilitinib. The pseudotyped VSV-GP also provided long-term remission in prostate cancer mouse models after intratumoral injections [101]. Furthermore, intravenous administration of subcutaneous tumors and bone metastases resulted in remission.…”
Section: Preclinical Studiesmentioning
confidence: 99%